Deaf children's bimodal bilingualism and education. (7th December 2015) - Swanwick, Ruth
Abstract : This paper provides an overview of the research into deaf children's bilingualism and bilingual education through a synthesis of studies published over the last 15 years. This review brings together the linguistic and pedagogical work on bimodal bilingualism to inform educational practice. The first section of the review provides a synthesis of the research, addressing linguistic, cognitive and social aspects of bimodal bilingualism. This is followed by a focus on bimodal bilingual language experience and use in different learning contexts. These first two sections provide the context for the main focus of the review: education and learning. The third section reports on links made between bimodal bilingualism and learning with regard to deaf children's literacy development. The fourth section examines further research into bimodal bilingual pedagogies. The final section considers the theoretical and practical implications of the field to date in developing a contemporary model of bimodal bilingual education for deaf children. It also charts future research priorities.